Slow Breathing Can Be Operantly Conditioned in the Rat and May Reduce Sensitivity to Experimental Stressors - Noble, Donald J.; Goolsby, William N.; Garraway, Sandra M.; Martin, Karmarcha K.; Hochman, Shawn (Frontiers in Physiology, 2017)
In humans, exercises involving slowed respiratory rate (SRR) counter autonomic sympathetic bias and reduce responses to stressors, including in individuals with various degrees of autonomic dysfunction. In the rat, we examined whether operant conditioning could lead to reductions in respiratory rate (RR) and performed preliminary studies to assess whether conditioned SRR was sufficient to decrease physiological and behavioral responsiveness to stressors. RR was continuously monitored during 20 two-hour sessions using whole body plethysmography. SRR conditioned, but not yoked control rats, were able to turn off aversive visual stimulation (intermittent bright light) by slowing their breathing below a preset target of 80 breaths/minute. SRR conditioned rats greatly increased the incidence of breaths below the target RR over training, with average resting RR decreasing from 92 to 81 breaths/minute. These effects were significant as a group and vs. yoked controls. Preliminary studies in a subset of conditioned rats revealed behavioral changes suggestive of reduced reactivity to stressful and nociceptive stimuli. In these same rats, intermittent sessions without visual reinforcement and a post-training priming stressor (acute restraint) demonstrated that conditioned rats retained reduced RR vs. controls in the absence of conditioning. In conclusion, we present the first successful attempt to operantly condition reduced RR in an animal model. Although further studies are needed to clarify the physio-behavioral concomitants of slowed breathing, the developed model may aid subsequent neurophysiological inquiries on the role of slow breathing in stress reduction.